Epigallocatechin-3-gallate in functional food development: From concept to reality. (August 2020) - Lai, Wing-Fu; Baig, Mirza Muhammad Faran Ashraf; Wong, Wing-Tak; Zhu, Bao Ting
Abstract: Background: Epigallocatechin-3-gallate (EGCG) is the most abundant and pharmaceutically active polyphenol in green tea. It shows diverse health-promoting effects, but due to its low oral bioavailability, its use in functional food development has been impeded. Over the years, the health-promoting effects of EGCG have been extensively reviewed; however, discussions of the possible use of EGCG in food development have been scant, even though copious ready-to-drink green tea beverages and nutritional supplements are available in the market. Scope and approach: The hopes and hypes involved in the use of EGCG in functional food development will be explored based on recent studies. Implications for future efforts to manipulate the properties of EGCG for food applications will be presented. Key findings and conclusions: Recent advances in technologies for structural modification and therapeutics delivery may enhance the food applications of EGCG. Despite this, justifications on the use of EGCG in functional food development should be seriously evaluated until a consensus is reached in terms of the safety and efficiency. Highlights: EGCG is the most abundant and pharmaceutically active polyphenol in green tea. In vitro and in vivo studies concerning EGCG show diverse health promoting effects. Chemical modification enhances the effect of EGCG on health promotion. Functional group conversion and glycoside modification are two major methods of modifying the EGCG structure. The use of EGCG in food development should be further evaluated in terms of safety and efficiency.